2014
DOI: 10.1108/mbe-10-2013-0052
|View full text |Cite
|
Sign up to set email alerts
|

Measuring value creation: VAIC and EVA

Abstract: Purpose: This study proposes a comparison between Value Added Intellectual Coefficient (VAIC) and one of the most important performance evaluation methods, the Economic Value Added (EVA), starting from a re-interpretation of the VAIC. Design/methodology/approach: The empirical data were gathered from AMADEUS Bureau van Dijk and consist of 2,596 companies operating in Northern Italy, from six different economic sectors, observed for the year 2011. A correlation analysis was carried out in order to highlight whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 19 publications
2
31
0
6
Order By: Relevance
“…In this regard, Bryant et al (2004) cite research that shows that both employees' actions and intangible assets, neither of which is captured by traditional performance measures, should be included in the assessment of a company's success. Iazzolino et al (2014) propose that a firm's performance must be measured not only by financial performance measures such as EVA but also through multi-criteria methodologies such as the Balanced Scorecard.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, Bryant et al (2004) cite research that shows that both employees' actions and intangible assets, neither of which is captured by traditional performance measures, should be included in the assessment of a company's success. Iazzolino et al (2014) propose that a firm's performance must be measured not only by financial performance measures such as EVA but also through multi-criteria methodologies such as the Balanced Scorecard.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies also compared different measurement models. For example, Iazzolino et al (2014) compared the VAIC and EVA models, focusing on Italian companies. The results indicate that scholars have extensively analysed VAIC, mainly connecting it with performance measurement in both developing and developed countries.…”
Section: General Criticisms Of the Vaic Modelmentioning
confidence: 99%
“…Given the objective of investigating how firms' performances could be re-interpreted by looking at two main perspectives, (i) intellectual capital and (ii) financial performances respectively (Iazzolino et al, 2014), an exploratory study design based on Euronext listed firms has been carried out by the authors. The main hypothesis on which this study was based is showed below: Tseng et al, 2013).…”
Section: Research Methodology Designmentioning
confidence: 99%